Partisipasi Masyarakat Dalam Pelaksanaan Musyawarah Rencana Pembangunan Di Desa Kolese Kecamatan Pasikolaga Kabupaten Muna - Milyani Milyani; Gunawan Gunawan; La Manguntara (Universitas Halu Oleo, 2021)
This study aims to determine community participation in the implementation of the village development plan deliberation (Musrenbang) in the Kolese Village, Pasikolaga District, Muna Regency and to find out the implementation of the village development plan deliberation (Musrenbang) in the Kolese Village, Pasikolaga District, Muna Regency. The method used in this research is descriptive qualitative research method, by means of observation, interviews and documentation. The results of this study are community participation at the time of the implementation of the development plan deliberation which was carried out in the Kolese Village, Pasikolaga District, Muna Regency, had involved the community at the Problem Identification stage, Planning stage, Decision Making stage and program implementation stage. However, the village government did not involve the community in the evaluation stage itself. The mechanism for implementing the Musrenbang in Kolese Village, Pasikolaga District, Muna Regency only runs two stages, namely the pre-Musrenbang stage and the Musrenbang implementation stage.